Cancer cell specific inhibition of Wnt/β-catenin signaling by forced intracellular acidification - Melnik, Svitlana; Dvornikov, Dmytro; Müller-Decker, Karin; Depner, Sofia; Stannek, Peter; Meister, Michael; Warth, Arne; Thomas, Michael; Muley, Thomas; Risch, Angela; Plass, Christoph; Klingmüller, Ursula; et al. (Cell discovery, 2018)
Use of the diabetes type II drug Metformin is associated with a moderately lowered risk of cancer incidence in numerous tumor entities. Studying the molecular changes associated with the tumor-suppressive action of Metformin we found that the oncogene SOX4, which is upregulated in solid tumors and associated with poor prognosis, was induced by Wnt/β-catenin signaling and blocked by Metformin. Wnt signaling inhibition by Metformin was surprisingly specific for cancer cells. Unraveling the underlying specificity, we identified Metformin and other Mitochondrial Complex I (MCI) inhibitors as inducers of intracellular acidification in cancer cells. We demonstrated that acidification triggers the unfolded protein response to induce the global transcriptional repressor DDIT3, known to block Wnt signaling. Moreover, our results suggest that intracellular acidification universally inhibits Wnt signaling. Based on these findings, we combined MCI inhibitors with H+ ionophores, to escalate cancer cells into intracellular hyper-acidification and ATP depletion. This treatment lowered intracellular pH both in vitro and in a mouse xenograft tumor model, depleted cellular ATP, blocked Wnt signaling, downregulated SOX4, and strongly decreased stemness and viability of cancer cells. Importantly, the inhibition of Wnt signaling occurred downstream of β-catenin, encouraging applications in treatment of cancers caused by APC and β-catenin mutations.
Gesehen am 26.03.2020